Moscow Centers for Sexual Well-Being: Market Structure and Legitimation Strategie - Pavel Demin (Journal of Economic Sociology, 2018)
The paper presents an overview of the Moscow market of centers of sexual well-being (CSWB), which construct a new niche in the market of psychological services, providing counseling services in matters of sexual and psychological well-being. Human notions of happiness and sexual well-being acquire there a commercial basis and become a good that can be purchased for a certain cost, like any product or service. Centers of sexual well-being use various strategies of legitimizing their activities to create a sustainable demand for their services. These legitimation strategies are deeply rooted in the culture of society and is a necessary condition for the centers’ work.During the research, a qualitative content analysis of the websites of eight centers of sexual well-being in Moscow was conducted. It was found out that this market today is small and underdeveloped, services are provided in the form of trainings and consultations, while there is no single standard of professions, education and seniority. The cost of training varies from 1500 rubles up to 80 000 rubles per person, while almost all the centers are targeted at the female target audience, and the attraction of new ones is due to various types of shares. On the basis of the coding matrix, the main strategies of legitimation were identified and described: the way to achieve happiness in the personal and family sphere (1); the tool for the development of human capital (2); the educational project of public discourse about sex (3) and the form of leisure (4). These strategies can be used by the centers together, they are not mutually exclusive.The overall result of the work is a detailed description of the CSWB market, the rules and principles for the functioning of market participants, a description of their legitimation strategies. This work can be useful for researchers interested in exploring new emerging markets, where demand is constructed by producers with the help of certain strategies of legitimating themselves and their specific “good”. In addition, this work is useful to all those who are interested in studying the organization of sexual well-being on a commercial basis and the associated spectrum of economic and psychological services.